2013
DOI: 10.1177/0272989x13500719
|View full text |Cite
|
Sign up to set email alerts
|

Providing Informal Care in Terminal Illness

Abstract: The most valued services are those that support carers in their caregiving role; however, supportive care preferences vary with the different circumstances of patients and carers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Current literature indicated several challenges that Canadian ICs often face when providing hospice and palliative care. [1][2][3][4] By exploring interventions and their effects on ICs delivering EOL care, several themes were developed that can be used to inform practice, policy, and research in Canada and beyond. Results suggest that current interventions in Canada can be improved to better support ICs providing hospice and palliative care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current literature indicated several challenges that Canadian ICs often face when providing hospice and palliative care. [1][2][3][4] By exploring interventions and their effects on ICs delivering EOL care, several themes were developed that can be used to inform practice, policy, and research in Canada and beyond. Results suggest that current interventions in Canada can be improved to better support ICs providing hospice and palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…However, providing informal care at the end of life comes with its own set of challenges. [2][3][4] ICs providing care for EOL patients experience more difficulties compared to non-EOL caregivers. 5 First off, studies have shown that caregivers providing hospice and palliative/EOL care can suffer from physical challenges, such as physical exhaustion and psycho-socio-spiritual challenges including anxiety and distress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods have also been used to determine priorities amongst patients accessing palliative care services and their caregivers. (4,(9)(10)(11) The International Access, Rights and Empowerment (IARE) study was carried out in Ireland, the UK and the USA with the aim of improving the rights of patients over the age of 65 accessing specialist palliative care services, and their families, through better understanding of their needs and the factors that help or hinder access to services. A DCE was undertaken to quantitatively evaluate patient preferences for services and supports when accessing palliative care, and to explore relationships between patient or healthcare system characteristics and patterns of preferences.…”
Section: Introductionmentioning
confidence: 99%
“…The previous literature shows that patients are swayed by recommendations from their physician [7,8] and by the influence of peers. [813] Patient characteristics included age, income, whether the patient is on monotherapy, and whether the patient reports difficulty remembering to administer eye drops. We expected that lower costs and longer intervals between injections will increase uptake of the new technology, and that patients will be more likely to adopt the new technology if their physician recommends it and/or if they think a large percentage of their peers are using it.…”
Section: Introductionmentioning
confidence: 99%